Modifying the Non-muscle Invasive Bladder Cancer Immune Microenvironment for Optimal Therapeutic Response - Annels, Nicola E.; Simpson, Guy R.; Pandha, Hardev (Frontiers in Oncology, 2020)
It is now well-recognised that the tumour microenvironment (TME) is not only a key regulator of cancer progression but also plays a crucial role in cancer treatment responses. Recently, several high-profile publications have demonstrated the importance of particular immune parameters and cell types that dictate responsiveness to immunotherapies. With this growing knowledge of TME-mediated therapy, approaches that increase therapeutic efficacy by remodelling the TME are actively being pursued. A classic example of this, in practice by urologists for over 40 years, is the manipulation of the bladder microenvironment for the treatment of non-muscle invasive bladder cancer (NMIBC) by instillation of intravesical bacillus Calmette-Guerin (BCG). The success of BCG treatment is thought to be due to its ability to induce a massive influx of Th1-polarized inflammatory cells, production of Th1 inflammatory cytokines and the generation of tumour-targeted Th1-mediated cytotoxic responses. Whilst BCG immunotherapy is still the most successful treatment for NMIBC, approximately 30% of patients are unresponsive to this treatment. Here we present a review highlighting a variety of promising alternative immunotherapies being developed that remodel the bladder TME. These include (1) the use of oncolytic viruses which selectively replicate within cancer cells whilst also modifying the immunological components of the TME, (2) manipulation of the bladder microbiome to augment the response to BCG or other immunotherapies (3) utilising Toll-like Receptor agonists as anti-tumour agents due to their potent stimulation of innate and adaptive immunity and (4)the growing recognition that immunotherapeutic strategies that will yield the greatest impact on patients may require multiple therapeutic approaches combined together. The accumulating knowledge on TME remodelling holds promise for providing an alternative therapy for patients with BCG-unresponsive NMIBC.